DLP 4D printing of multi-responsive bilayered structures - Mainik, Philipp; Hsu, Li-Yun; Zimmer, Claudius W.; Fauser, Dominik; Steeb, Holger; Blasco, Eva (Advanced Materials Technologies, 2023)
Advances in soft robotics strongly rely on the development and manufacturing of new responsive soft materials. In particular, light-based 3D printing techniques, and especially, digital light processing (DLP), offer a versatile platform for the fast manufacturing of complex 3D/4D structures with a high spatial resolution. In this work, DLP all-printed bilayered structures exhibiting reversible and multi-responsive behavior are presented for the first time. For this purpose, liquid crystal elastomers (LCEs) are used as active layers and combined with a printable non-responsive elastomer acting as a passive layer. Furthermore, selective light response is incorporated by embedding various organic dyes absorbing light at different regimes in the active layers. An in-depth characterization of the single materials and printed bilayers demonstrates a reversible and selective response. Last, the versatility of the approach is shown by DLP printing a bilayered complex 3D structure consisting of four different materials (a passive and three different LCE active materials), which exhibit different actuation patterns when irradiated with different wavelengths of light.
Online veröffentlicht: 17 June 2023
Gesehen am 15.07.2024